PERILAKU KONSUMEN DALAM PEMBELIAN BAKSO DI MALANG - Budi Hartono; Umi Wisapti Ningsih; Nila Fithria Septiarini (Buletin Peternakan, 2011)
The objective of this research were to analyzed the characteristics and the factors influencing the purchasing of meatballs in Malang. The research was conducted in Malang, East Java in March 2011. One hundred and twenty consumers were chosen as respondents by Accidental Sampling method. Data were analyzed by descriptive and factor analyses. The results showed that most customers were women, student status, with the age below 35 years old, and incomes level of IDR 1.000.000,00 into IDR 2.000.000,00 per month. The meatball`s price was affordable by the consumers. The meatball`s purchasing patterns showed that the meatball was consumed not as a main meal but only for culinary, hobby and also as snacks. The eight factors considered by consumers of meatball purchasing consecutively were price, social class, accessibility, parking, display presentation, satisfaction, income and demographics, respectively.(Key words: Consumer`s behavior, Considerance factor, Meatball)